Hemodialysis Procedure–Associated Autonomic Imbalance and Cardiac Arrhythmias: Insights From Continuous 14‐Day ECG Monitoring. Issue 19 (1st October 2019) - Rogovoy, Nichole M.; Howell, Stacey J.; Lee, Tiffany L.; Hamilton, Christopher; Perez‐Alday, Erick A.; Kabir, Muammar M.; Zhang, Yanwei; Kim, Esther D.; Fitzpatrick, Jessica; Monroy‐Trujillo, Jose M.; Estrella, Michelle M.; Sozio, Stephen M.; et al.
Abstract : Background: In patients with end‐stage kidney disease, sudden cardiac death is more frequent after a long interdialytic interval, within 6 hours after the end of a hemodialysis session. We hypothesized that the occurrence of paroxysmal arrhythmias is associated with changes in heart rate and heart rate variability in different phases of hemodialysis. Methods and Results: We conducted a prospective ancillary study of the Predictors of Arrhythmic and Cardiovascular Risk in End Stage Renal Disease cohort. Continuous ECG monitoring was performed using an ECG patch, and short‐term heart rate variability was measured for 3 minutes every hour (by root mean square of the successive normal‐to‐normal intervals, spectral analysis, Poincaré plot, and entropy), up to 300 hours. Out of enrolled participants (n=28; age 54±13 years; 57% men; 96% black; 33% with a history of cardiovascular disease; left ventricular ejection fraction 70±9%), arrhythmias were detected in 13 (46%). Nonsustained ventricular tachycardia occurred more frequently during/posthemodialysis than pre‐/between hemodialysis (63% versus 37%, P =0.015). In adjusted for cardiovascular disease time‐series analysis, nonsustained ventricular tachycardia was preceded by a sudden heart rate increase (by 11.2 [95% CI 10.1–12.3] beats per minute; P <0.0001). During every‐other‐day dialysis, root mean square of the successive normal‐to‐normal intervals had a significant circadian pattern (Mesor 10.6 [ 95% CI 0.9–11.2] ms; amplitude 1.5 [95% CI 1.0–3.1] ms; peak at 02:01 [95% CI 20:22–03:16] am ; P <0.0001), which was replaced by a steady worsening on the second day without dialysis (root mean square of the successive normal‐to‐normal intervals −1.41 [95% CI −1.67 to −1.15] ms/24 h; P <0.0001). Conclusions: Sudden increase in heart rate during/posthemodialysis is associated with nonsustained ventricular tachycardia. Every‐other‐day hemodialysis preserves circadian rhythm, but a second day without dialysis is characterized by parasympathetic withdrawal.